[Spanish translation] Understanding the dimensions of athlete brand authenticity - Hasaan, Ali (2022)
The management of an athlete brand is challenging due to the complex nature of athlete career and life. Striving to maintain brand authenticity will promote long-term sustainability of the brand. The purpose of the study is to determine possible factors that contribute to athlete brand authenticity and help athletes to develop their brand more authentically. To understand the concept of athlete brand authenticity, a systematic literature review was conducted on various electronic databases. The study opted the five-step stages of the framework for this systematic review. A total of 76 attributes were identified from past studies that analyzed the attributes of brand authenticity for various brands. After merging interrelated attributes, the final number of unique attributes was 23. These attributes were distributed among three major themes: on-field activities, off-field activities and marketing activities of an athlete. The study finds brand authenticity to be a multi-dimensional and complex process that endures for longer extensive periods of an athlete’s career. The current study also highlights the complications related to an athlete brand that occur when establishing athlete brand authenticity. Therefore, this study provides an opportunity to refine athlete brand authenticity further within the discussed domains.